Cellulose Aggregation under Hydrothermal Pretreatment Conditions - Silveira, Rodrigo L; Stoyanov, Stanislav R; Kovalenko, Andriy; Skaf, Munir S (Biomacromolecules, 2016)
Cellulose, the most abundant biopolymer on Earth, represents a resource for sustainable production of biofuels. Thermochemical treatments make lignocellulosic biomaterials more amenable to depolymerization by exposing cellulose microfibrils to enzymatic or chemical attacks. In such treatments, the solvent plays fundamental roles in biomass modification, but the molecular events underlying these changes are still poorly understood. Here, the 3D-RISM-KH molecular theory of solvation has been employed to analyze the role of water in cellulose aggregation under different thermodynamic conditions. The results show that, under ambient conditions, highly structured hydration shells around cellulose create repulsive forces that protect cellulose microfibrils from aggregating. Under hydrothermal pretreatment conditions, however, the hydration shells lose structure, and cellulose aggregation is favored. These effects are largely due to a decrease in cellulose–water interactions relative to those at ambient conditions, so that cellulose–cellulose attractive interactions become prevalent. Our results provide an explanation to the observed increase in the lateral size of cellulose crystallites when biomass is subject to pretreatments and deepen the current understanding of the mechanisms of biomass modification.